Seeking Intimacy in the 'Wooing Group' - Lazikani, A (Penn State University Press, 2017)
This essay examines the five lyrical meditations known collectively as the Wooing Group, focusing on the anchoritic reader’s nurturance of her affective literacies in reading these texts. The presence-absence of the Lover Christ and the Virgin Mary is central to the affective strategies of the meditations: the anchoress is engaged in a continual search for Christ and his Mother, drawing close to them only to find herself distanced again.